Apical Sealing Ability of Two Calcium Silicate-Based Sealers Using a Radioactive Isotope Method: An In Vitro Apexification Model - Pereira, Inês Raquel (2021)
The aim of this study was to evaluate and compare the sealing ability of two calcium silicate-based sealers (TotalFill BC RRM Fast Set Putty and White ProRoot MTA) when used as apical plugs in immature teeth through nuclear medicine. Single-rooted extracted teeth (n = 34) had their crowns and root tip sectioned to obtain 14 mm long root segments to simulate an in vitro apexification model. Were created two experimental groups, namely MTA (n = 12) and BC (n = 12), and two control groups, PG (positive group, n = 5) and NG (negative group, n = 5). On the 4th day after placing the respective apical plug, the apical portions of the teeth were submerged in a solution of sodium pertechnetate (99mTcNaO4) for 3 h. Statistical analysis showed a significant difference between the MTA group and the controls (p < 0.05). The BC group had a significant difference regarding the negative control (p < 0.001) but showed no statistical significance regarding the positive control (p = 0.168). There was a statistically significant difference (p = 0.009) between the BC group (7335.8 ± 2755.5) and the MTA group (4059.1 ± 1231.1), where the last showed less infiltration. Within the limitations of this study, White ProRoot MTA had a significantly better sealing ability than TotalFill BC RRM Fast Set Putty.